(untitled) (Faridpur Medical College Journal, 2016)
Very low birth weight (VLBW) is an important cause of infant mortality and still a challenge for achieving Millennium Development Goal (MDG) in Bangladesh. Our study was to see the risk factors and its outcome of VLBW neonates in a tertiary level Faridpur Medical College Hospital (FMCH), outside capital Dhaka. This prospective cross sectional study was conducted in neonatal Unit of pediatric department in FMCH. All neonates who were admitted here had been selected and we find out the very low birth weight neonates for our study purpose. All anthropometric measurements were taken by us in our department. We took all the informations about neonates within our study period of six months (November 2013 to April 2014) through a prescribed protocol. Total 1126 neonates admitted within our study period of 6 months. Among 1126 neonates 76 of them were VLBW. Among 76 VLBW neonates 38 (50%) were male and 38 (50%) were female, but 22 of them were expired, which was 28.94% of total VLBW neonates. Most expired on month of March which was 38.46%. Among expired VLBW neonates 10 (45.45%) of them were male and 12 (54.55%) of them were female. Total 48 (63.15%) mothers of VLBW neonates delivered at hospital of them Caesarean section occurs in 40 (52.63%) mothers of VLBW neonates and normal vaginal delivery (NVD) occurs in 36 cases (47.37%). Home delivery occurs in mothers of 28 VLBW neonates. Among them 15 (53.57%) were done by traditional birth attendance (TBA), 8 (28.57%) by local dai and 5 (17.86%) by relatives of the family of VLBW neonates. We found mothers of 41 (53.95%) VLBW neonates had premature rupture of membrane (PROM), 8 (10.53%) had eclampsia, 4 (5.26%) had leaking membrane and 4 (5.26%) had history of accident. Maternal age of VLBW neonates are more common between 18 to 24 years of age that was 53.95% (41 in number) but 27 mothers (35.52%) were below 18 years of age . We found in our study that the survival rate of VLBW neonates in our institute is not like developed countries but it is better than many developing countries around the world. Faridpur Med. Coll. J. Jan 2016;11(1): 15-19